2021
DOI: 10.1186/s12939-021-01387-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the health of refugee women: a scoping literature review incorporating the social ecological model

Abstract: The health of refugee women after settlement in a new country, can be adversely or positively affected by individual, interpersonal, community, and organizational factors. While much of the previous literature highlights these factors individually, there is a lack of comprehensive synthesis regarding how the factors interact to influence the health of refugee women. We conducted a thematic analysis in our literature review to elucidate how providers can work with refugee women to prevent adverse health outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 50 publications
0
50
0
1
Order By: Relevance
“…The present study has several strengths. First, by approaching mental health with a clear gender perspective, the study mitigates a key limitation in refugee research to date, namely the paucity of gender-specific data and evidence ( 40 , 41 ). The findings on gender-specific effects of stress in the resettlement phase may be applied in practice to support and promote gender-sensitive resettlement strategies and initiatives, as well as facilitate research focusing on identifying predictors of well-being outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study has several strengths. First, by approaching mental health with a clear gender perspective, the study mitigates a key limitation in refugee research to date, namely the paucity of gender-specific data and evidence ( 40 , 41 ). The findings on gender-specific effects of stress in the resettlement phase may be applied in practice to support and promote gender-sensitive resettlement strategies and initiatives, as well as facilitate research focusing on identifying predictors of well-being outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study on Afghan refugee in the US which tested whether social support modified the association between perceived discrimination and psychological distress, did not find any evidence to support this ( 38 ). Refugee women in particular have acknowledged the importance of social support in adapting to their lives in the host country and report that they face barriers to maintaining it in the resettlement phase, both within their own ethnic community and in the host community, often due to language barriers ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in regard to ‘migrant’ versus ‘refugee’, Castañeda and Holmes note that “[w]hether a person is identified as a refugee or as some other socially constructed category… depends on historical, sociocultural, political, and economic contexts” [ 27 ]. Thus, the question of choice remains debated among migrants and refugees and the definitions are not “rigid” [ 27 29 ]. This is not to say that there is not a difference between a refugee fleeing persecution and a migrant accepting a job in another country, rather that the matter is not easily defined.…”
Section: Introductionmentioning
confidence: 99%
“…Congolese migrant women in the USA have also, together with researchers, used the CBPR approach for health promotion, resulting in photo and story sharing on themes such as healthcare system issues, social support, and daily experiences of health [ 26 ]. Furthermore, review studies have concluded that community work for migrant women can include the initiation of dialogue and collaboration to increase community social support, which can prevent isolation as well as improving mental health and access to healthcare [ 27 ]. Many stressors, such as housing or work, may affect health among migrant women, and social support may work as a resilience strategy in handling various situations [ 28 ].…”
Section: Introductionmentioning
confidence: 99%